Intestinal atresia: a case report - admin, admin (2018)
The fetal intestinal tract can be altered by many disease processes, typical ultrasound findings of bowel obstruction are dilated bowel loops in the fetal abdomen proximal to the obstruction. Although intestine dilation occasionally can be seen, most bowel dilation cases are in the small intestine. Early diagnosis is possible for some sites proximal obstruction, such as duodenal and esophageal atresia. Of all the intestinal atresias 39% corresponds to the jejunum and ileum is the most common cause of congenital bowel obstruction and these only in the 50-60% ultrasound findings are given. The objective of this paper is to present and discuss how review the diagnosis, evaluation and perinatal outcome of a case of intestinal atresia and its differential diagnosis.